Rancang Bangun Pembangkit Listrik Tenaga Surya (PLTS) pada Gerobak UMKM Berbasis Internet Of Things (IOT) - Nova Ardila; Jefri Lianda; Hikmatul Amri; Adam Adam; Khairudinsyah Khairudinsyah (Universitas Pahlawan Tuanku Tambusai, 2026)
The utilization of Solar Power Plants (PLTS) for micro, small, and medium enterprises (MSMEs) is an effective solution to provide an independent, environmentally friendly, and sustainable electrical energy source. This study aims to design and develop an Internet of Things (IoT)-based solar power system for MSME carts that is capable of supplying electrical energy while providing real-time monitoring of electrical parameters. An experimental method was employed through hardware and software design, system assembly, and performance testing. The proposed system consists of a solar panel, solar charge controller, battery, inverter, voltage and current sensors, and a NodeMCU ESP8266 microcontroller for transmitting monitoring data to an IoT platform. System testing was conducted from 08:00 to 17:00 to evaluate variations in voltage, current, and panel temperature under different levels of solar radiation. The results indicate that the solar panel voltage gradually increased and reached a maximum value of 20.0 V at 12:00, before decreasing as solar radiation declined in the afternoon. The Battery Charge Regulator (BCR) maintained a relatively stable output voltage despite fluctuations in the input voltage from the solar panel. Furthermore, the IoT-based monitoring system successfully displayed voltage, current, and temperature data accurately, continuously, and in real time through a monitoring interface, enabling users to monitor system performance remotely. These findings demonstrate that the proposed IoT-based solar power system operates effectively as an independent energy source and supports more efficient energy management for MSME carts.